2003
DOI: 10.4049/jimmunol.170.3.1452
|View full text |Cite
|
Sign up to set email alerts
|

CCL28 Has Dual Roles in Mucosal Immunity as a Chemokine with Broad-Spectrum Antimicrobial Activity

Abstract: CCL28 is a CC chemokine signaling via CCR10 and CCR3 that is selectively expressed in certain mucosal tissues such as exocrine glands, trachea, and colon. Notably, these tissues commonly secrete low-salt fluids. RT-PCR analysis demonstrated that salivary glands expressed CCL28 mRNA at the highest levels among various mouse tissues. Single cells prepared from mouse parotid glands indeed contained a major fraction of CD3−B220low cells that expressed CCR10 at high levels and CCR3 at low levels and responded to CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
270
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(286 citation statements)
references
References 37 publications
15
270
1
Order By: Relevance
“…After washing, cells were incubated with streptavidin-allophycocyanin for 30 min. For surface staining of CCR9, CCR10, and CXCR4, mouse CCL25-Fc, human CCL27-Fc, mouse CXCL12-Fc, respectively, and control Fc were used, as described previously (13). After staining, cells were immediately analyzed on a FACSCalibur (BD Biosciences, Mountain View, CA).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…After washing, cells were incubated with streptavidin-allophycocyanin for 30 min. For surface staining of CCR9, CCR10, and CXCR4, mouse CCL25-Fc, human CCL27-Fc, mouse CXCL12-Fc, respectively, and control Fc were used, as described previously (13). After staining, cells were immediately analyzed on a FACSCalibur (BD Biosciences, Mountain View, CA).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…This was performed using 8-m Transwell plates (Corning Costar, Cambridge, MA), as described previously (13). Briefly, cells were placed in upper wells (2 ϫ 10 6 /well), while bottom wells contained medium alone or medium containing chemokines at concentrations that were predetermined to be optimal (300 nM for CCL25, 300 nM for CCL28, and 50 nM for CXCL12) (13,14).…”
Section: Chemotaxis Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…13 Although little is known about the regulation of CCL28, it has been shown to mediate both eosinophil and T-cell recruitment in vitro, in addition to playing a role in mucosal immunity because of potent broad-spectrum antimicrobial activity. [13][14][15] CCL28, like CCL27, has been identified as a ligand for CCR10/GPR2 13 however Pan and colleagues 14 have demonstrated that the functional effects of CCL28 are also mediated by CCR3. We investigated the pattern of CCL28 expression within normal and allergen-challenged lungs and examined the role of CCL28 in a murine model of allergic airway inflammation.…”
mentioning
confidence: 99%